The complete genome sequence and comparative effectorome of Sporisorium panici-leucophaei: the causal smut disease agent in sourgrass (Digitaria insularis) - Crestana, Gustavo Schiavone (2020)
Fungi of the Ustilaginaceae family are the main causal agents of smut disease in Poaceae plants, resulting in significant agronomic and economic losses. Smut species have a biotrophic lifestyle, which depends on a close interaction with a host to complete their life cycle and produce spores (2n). The fungus Sporisorium panici-leucophaei (Spl) infects and colonizes Digitaria insularis seedlings, causing the disease known as sourgrass smut disease. Despite presenting a similar life cycle compared to other smuts, scarce information is available about this pathosystem in the scientific literature. The development of a whip-like structure from the apex of sourgrass plants reveals potential for comparing with the sugarcane smut disease pathosystem. In this sense, the present work evaluated the colonization patterns in planta, the life cycle and formation of typical penetration structures of S. panici-leucophaei. In addition, complete genome sequencing of the S. panici-leucophaei was completed using two distinct sequencing platforms. The characterization of S. panici-leucophaei life cycle in vitro was concluded with the detection of distinct phases, such as spore germination, probasidium formation, sporidia formation and dikaryotic hyphae visualization In addition, it was possible to quantitatively establish the in planta infection time-course by spore germination 8 hours post-inoculation (hpi); appressorium formation at 48 hpi and hyphae detection at 72 hpi. The S. panici-leucophaei genome was completely assembled by generating a 22 chromosome assembly plus mitochondrial DNA. In addition, 6,404 genes were predicted, of which 382 were secreted along with 66 candidate effector genes, a pattern similar to that found for the S. scitamineum fungus. Comparative genomic analyses with the sugarcane smut genome yielded the first insights into shared and specific gene-content and provided useful information on a poorly studied plant pathogen.